STATUS HUKUM SUATU ANAK PERUSAHAAN DALAM HUKUM PERDATA - Misrijal Misrijal (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT          The business of a company sometimes is so big and wide so that the company itself needs to be broken down according to business classification. But it is also to ensure that the needs of the business that has been broken down, which each will become an independent Limited Company is still in the same ownership by controlling the still centralized within certain limits. To that end, fragments of these companies (subsidiaries) together with other companies that have already existed, with the same owner, or at least there is a special relationship that is owned and led by an independent company as well. Company owner (and pengomando) is called by a holding company or parent company. In the business world, a company does not always go well, and often finances are getting worse, so that the company is no longer able to pay its debts.Although from the point of economic activities of companies in the group is a unity, but in terms of juridical each company member in the group has its own characteristics, namely that each company that joined the group company is a separate legal entity. If one of the subsidiaries committed themselves to third parties, shareholders participate responsible for the repayment of the debt.The merger between the companies with other companies in general as part of efforts to restructure the company. The company's restructuring mencapa usually done for the purpose, among others, improve the performance of the company, preparing to face the competition strengthen the company's capital or assets, to avoid losses, avoid destruction, avoid bankruptcy, as well as the capital increase.The research method used in this thesis is a normative law research. Ie normative legal research methods or by researching existing library materials. The nature of the research is descriptive research that is a form of research that aimed to describe the phenomena that exist, whether a natural phenomenon or man-made phenomenon. Source data used are secondary data, which consists of primary legal materials, secondary, and tertiary. The data collection was done by a literature study (library reseacrh) and data gathered, secondary data, and then processed and analyzed by using qualitative methods of analysis techniques. Keywords: Status, Company.